2010 10th IEEE International Conference on Computer and Information Technology 2010
DOI: 10.1109/cit.2010.306
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Power Consumption Analysis of DVFS-Enabled H.264 Decoder on Heterogeneous Multi-Core Platform

Abstract: Power consumption becomes a very important criterion for the portable embedded devices and, therefore, many Dynamic Voltage/Frequency Scaling (DVFS) techniques have been introduced. This paper is trying to break down and analyze the power consumed by three main components, DSP logic, local memory, and the external DDR2, of a multi-core SoC platform. There are four configurations for this SoC platform: one DSP with full and half clock rates and two DSP's with full and half clock rates. The DSP's in the SoC are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…With a special software application, the two high-performance processor cores are disabled and the two low-power processor cores are set to high-performance processing because initial tests showed that at least two processors need to be enabled for fluid playback. This setting is chosen to reduce the effect of dynamic voltage and frequency scaling (DVFS, [40]). Furthermore, the performance governor of the GPU is also set to 'performance'.…”
Section: B Dutsmentioning
confidence: 99%
“…With a special software application, the two high-performance processor cores are disabled and the two low-power processor cores are set to high-performance processing because initial tests showed that at least two processors need to be enabled for fluid playback. This setting is chosen to reduce the effect of dynamic voltage and frequency scaling (DVFS, [40]). Furthermore, the performance governor of the GPU is also set to 'performance'.…”
Section: B Dutsmentioning
confidence: 99%
“…At the same time it has to be ensured that no other process, like idle power or background system processes, disturb the measurements. Such setups have, e.g., been proposed in [2], [3], [4], or [5].…”
Section: Introductionmentioning
confidence: 99%